Blood flow alterations in TNBS-induced colitis: Role of endothelin receptors - (:unkn) unknown (SPRINGER BASEL AG, 2004)
Objectives:The aim of the present study was to investigate the time dependent changes in hemodynamic parameters and to assess the role of endothelin (ET) receptors in trinitrobenzene sulfonic acid (TNBS) induced colitis. Materials:Inferior mesenteric artery (IMA) hemodynamics, myeloperoxidase activity (MPO) and damage scores were measured immediately or 1, 3, 5 and 14 days after colitis. Treatments: Another group of rats received a nonselective ET receptor antagonist bosentan (30 mg/kg/day), ET-A receptor antagonist BQ485 (60 mug/rat/day) or ET-B receptor antagonist BQ788 (60 mug/rat/day) prior to and on the 1st, 2nd and 3rd days after TNBS administration. Results:IMA flow significantly increased at 90 min followed by a substantial decrease through days 1-5. Tissue MPO activity and macroscopic damage score increased on 1st day after the induction of colitis and remained elevated 3, 5 and 14 days following colitis. Treatment with bosentan or ET-A receptor antagonist largely prevented the colitis-induced reduction in blood flow and tissue injury whereas ET-B receptor antagonist did not attenuate tissue injury or reductions in blood flow. Conclusions:Our results demonstrate that time-dependent abnormalities occur in IMA hemodynamics following TNBS administration. Our findings also indicate that ET-A receptors but not ET-B receptors play an important role in the colonic inflammation following TNBS administration.
Keywords: TNBS; IBD; BQ-485; BQ788; endothelins; ischemia; colitis; intestinal inflammation; INFLAMMATORY BOWEL-DISEASE; ACID-INDUCED COLITIS; RAT SMALL-INTESTINE; CROHNS-DISEASE; ULCERATIVE-COLITIS; ISCHEMIC-INJURY; MUCOSAL INJURY; MICROCIRCULATION; VASOCONSTRICTION; PATHOGENESIS